2020
DOI: 10.1186/s12961-019-0522-2
|View full text |Cite
|
Sign up to set email alerts
|

A scoping review of the uses and institutionalisation of knowledge for health policy in low- and middle-income countries

Abstract: There is growing interest in how different forms of knowledge can strengthen policy-making in low-and middleincome country (LMIC) health systems. Additionally, health policy and systems researchers are increasingly aware of the need to design effective institutions for supporting knowledge utilisation in LMICs. To address these interwoven agendas, this scoping review uses the Arskey and O'Malley framework to review the literature on knowledge utilisation in LMIC health systems, using eight public health and so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
36
0
7

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(44 citation statements)
references
References 77 publications
1
36
0
7
Order By: Relevance
“…15 Recent reviews of experience from both LMIC and higher income countries settings have, however, concluded that further research is needed to understand how processes of institutionalizing knowledge use/knowledge mobilization develop over time, as well as to consider their health system and wider impacts. 7,13,16,17 This paper seeks, therefore, to contribute to current literature by describing an experience of knowledge coproduction/mobilization for health system development, from Cape Town, South Africa. An embedded HPSR huba collaboration between 2 universities [2] -was established in 2012 to, amongst other things, draw 'the tacit knowledge of experienced practitioners into the task of better understanding health policy and health systems, and how to strengthen policy implementation and system performance' (CHESAI proposal 2012).…”
Section: Key Messagesmentioning
confidence: 99%
See 2 more Smart Citations
“…15 Recent reviews of experience from both LMIC and higher income countries settings have, however, concluded that further research is needed to understand how processes of institutionalizing knowledge use/knowledge mobilization develop over time, as well as to consider their health system and wider impacts. 7,13,16,17 This paper seeks, therefore, to contribute to current literature by describing an experience of knowledge coproduction/mobilization for health system development, from Cape Town, South Africa. An embedded HPSR huba collaboration between 2 universities [2] -was established in 2012 to, amongst other things, draw 'the tacit knowledge of experienced practitioners into the task of better understanding health policy and health systems, and how to strengthen policy implementation and system performance' (CHESAI proposal 2012).…”
Section: Key Messagesmentioning
confidence: 99%
“…23,26,28 Although the macro, societal-level impacts of the JC and linked engagements are inevitably harder to discern, it can be argued that they are likely to flow from the sorts of policy and organizational changes initiated within the WCG:H and CityHealth discussed above. 16 JC thinking is also acknowledged by managers as feeding into the wider processes of co-creating organizational and health service re-design (Figure 1), that will have long-lasting impacts on the provincial health system. Similarly, the universities' wider teaching and leadership development activities have potential system impacts and societal level benefits (Box 4).…”
Section: Post-graduate Teaching Programmes Have Been Infusedmentioning
confidence: 99%
See 1 more Smart Citation
“…This aspect can justify the popularity of some not-for-profit entities as a reliable (public advisory system). 3 In this context, Syria may represent a factual example. The role of non-governmental scientific initiatives in the Middle East was proven, as some of them showed their attractivity in societies which mostly lack public non-political unbiased scientific platforms that may fill the gap between original scientific sources and a non-English speaking population.…”
mentioning
confidence: 99%
“…The content was created depending on reliable sources and continuously updated data. 3 Importantly posting short, shareable bullet points was an e ective approach to get massive attention, particularly under quarantine and confinement statues.…”
mentioning
confidence: 99%